1991
DOI: 10.1083/jcb.115.5.1437
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous muscle lectin inhibits myoblast adhesion to laminin.

Abstract: Abstract. L-14, a dimeric lactose-binding lectin with subunits of 14 kD, is expressed in a wide range of vertebrate tissues. Several functions have been postulated for this lectin, but definitive evidence for a specific biological role has been elusive . In muscle, L-14 is secreted during differentiation and accumulates with laminin in basement membrane surrounding each myofiber. Here we present evidence that laminin is a major s differentiating cells integrate into complex tissues, their changing interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0
10

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(134 citation statements)
references
References 89 publications
5
119
0
10
Order By: Relevance
“…In accordance with their proposed functions, lectins enhance or inhibit cell matrix interactions. Although little is known about the exact role of lectins in regulating cell adhesion, current models suggest that binding of lectins to matrix proteins elicits an inhibitory effect due to a steric hindrance of cell-matrix interactions [10,11]. The latter depend to a large extent upon the engagement of specific extra-cellular matrix proteins with cell surface integrins [12][13][14].…”
Section: Xcl Induces Actin Cytoskeleton Modificationsmentioning
confidence: 99%
“…In accordance with their proposed functions, lectins enhance or inhibit cell matrix interactions. Although little is known about the exact role of lectins in regulating cell adhesion, current models suggest that binding of lectins to matrix proteins elicits an inhibitory effect due to a steric hindrance of cell-matrix interactions [10,11]. The latter depend to a large extent upon the engagement of specific extra-cellular matrix proteins with cell surface integrins [12][13][14].…”
Section: Xcl Induces Actin Cytoskeleton Modificationsmentioning
confidence: 99%
“…That LAMPs, along with the extracellular matrix components fibronectin and laminin, are a major cellular carrier of polylactosamine glycosylation suggests that their surface expression is involved in lectin-mediated cell adhesion Sato and Hughes, 1992). Polylactosamines of laminin are recognized by both 14-and 31-kDa endogenous f-galactoside binding lectins, and lectin secretion regulates cellular binding to polylactosamines of laminin (Woo et al, 1990;Zhou and Cummings, 1990;Cooper et al, 1991;Ochieng et al, 1992;Sato and Hughes, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…As OECs continue to differentiate during fetal stages of development, they begin to express the L14 lectin (Mahanthappa et al, 1994) and the O4 antigenic epitope (Doucette and Devon, 1994;Franceschini and Barnett, 1996). The L14 lectin binds to molecules containing polylactosamine chains (Zhou and Cummings, 1993;Cooper et al, 1991) and was shown by Mahanthappa et al (1994) to promote the adhesion of primary olfactory neurons to laminin in vitro in an integrin-independent manner. The O4 mouse monoclonal antibody (Sommer and Schachner, 1981) recognizes a cell surface epitope that is also expressed by glial cells in the O 2 A lineage (Gard and Pfeiffer, 1989;Trotter and Schachner, 1989) and by Schwann cells (Mirsky et al, 1990;Morgan et al, 1991).…”
Section: Oecs Normally Differentiate Into Nonmyelinating Gliamentioning
confidence: 99%